Perbandingan Prestasi Sekolah Anak Bijak Dengan Anak Tanpa Batas Digital Dalam Konsumsi Media Sosial Di Banda Aceh - Mulia Zahrani; Desy Fadhillah; Rizqa Qurrati A'yuni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study analyzes how the advancement of digital technology has led to increased social media usage among children. This trend has both positive and negative impacts on a child's development and performance, depending on how the technology is used. The study aims to compare the performance of children whose social media usage is restricted (digitally wise children) with those who use social media without restrictions in Banda Aceh. A qualitative approach utilizing field research methods was employed. Data collection involved observation, interviews, and documentation. Informants were selected using purposive sampling, comprising six children: three subject to restrictions on digital media usage and three with no restrictions. The findings indicate that children who receive guidance and have restrictions placed on their digital media usage demonstrate better reading skills, greater focus during study, better emotional control, and higher levels of engagement in both academic and non-academic activities. Conversely, children who use digital media without restrictions tend to struggle with concentration, spend more time in front of screens, and participate less in learning and social activities. The study concludes that digital media usage does not necessarily have negative consequences when accompanied by parental supervision and guidance. Therefore, age-appropriate restrictions on digital media usage are crucial for supporting a child's academic, social, emotional, and character development.